Portugiesische grammatik - Hundertmark-Santos Martins, Maria Teresa (De Gruyter, 2014)
This systematic overview of the grammatical features of the Portuguese language is geared to the specific needs and problems of German-speaking students of Portuguese. Taking into account the recent Portuguese spelling reform, the new edition offers updated as well as additional linguistic examples and explanations.